If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -3 = 16x + -73 Reorder the terms: -3 + 6x = 16x + -73 Reorder the terms: -3 + 6x = -73 + 16x Solving -3 + 6x = -73 + 16x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-16x' to each side of the equation. -3 + 6x + -16x = -73 + 16x + -16x Combine like terms: 6x + -16x = -10x -3 + -10x = -73 + 16x + -16x Combine like terms: 16x + -16x = 0 -3 + -10x = -73 + 0 -3 + -10x = -73 Add '3' to each side of the equation. -3 + 3 + -10x = -73 + 3 Combine like terms: -3 + 3 = 0 0 + -10x = -73 + 3 -10x = -73 + 3 Combine like terms: -73 + 3 = -70 -10x = -70 Divide each side by '-10'. x = 7 Simplifying x = 7
| 24+76+(65-12)= | | 14y=13(y+17) | | 3x+38=11x-50 | | 2x-6=6+12x | | 4x-5y-3=32 | | d^2+2d=99 | | 4h^2+49=28h | | 10=16t^2+70t+10 | | 2x+5=x+(-5) | | -2500-200x=-12000 | | 34(23x+34)+45x= | | -2500-200x=-1200 | | r^2-r-10=0 | | 8x+18=14x | | -2500-200x=-5100 | | 3(2x+3)+3x=12 | | 0=4x-5 | | y=4(3)-5 | | -4x+15=9-6x | | y=4(2)-5 | | 34-4x=5x+17 | | 3x-(30+8-7)*6x=13 | | 7-7x=79-21x | | 5-7x=81-21x | | 2(3x+2)= | | 0.27(18)+0.03x=0.09(6+x) | | 12+(-3)= | | 2-x=4-14 | | (2x^8)(-3x^8)(4x^8)= | | ln(4x)+ln(x)=5 | | 3x+142=10x-5 | | 11cos(0)=11 |